2022
DOI: 10.1109/access.2021.3120718
|View full text |Cite
|
Sign up to set email alerts
|

Preserving Operation Frequency Privacy of Incumbents in CBRS

Abstract: Citizens Broadband Radio Service (CBRS) is a novel service band in the United States, spanning 3550 − 3700 MHz, recently opened for commercial cognitive operations. The CBRS has a three tier hierarchical architecture, wherein, the topmost tier users (also called as incumbents) include military radars. The second and third tier facilitate licensed and unlicensed access to the band, respectively. The privacy of incumbents has been a major concern and different schemes have been proposed in the literature to pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The performance of the proposed heuristic has been tested for the location privacy use case, and it has been shown that the ARC closely approximates the optimal solution for small-scale settings. In [98], a generalization of the operation frequency privacy preserving framework in [96] to a more practical three-tier CBRS has been proposed. However, a joint evaluation for the privacy of the location and operational parameters of the incumbents is still required.…”
mentioning
confidence: 99%
“…The performance of the proposed heuristic has been tested for the location privacy use case, and it has been shown that the ARC closely approximates the optimal solution for small-scale settings. In [98], a generalization of the operation frequency privacy preserving framework in [96] to a more practical three-tier CBRS has been proposed. However, a joint evaluation for the privacy of the location and operational parameters of the incumbents is still required.…”
mentioning
confidence: 99%